Evaluating the Incidence of Postoperative Pancreatic Fistula after Pancreaticojujenostomy among the Cases of Whipple Surgery - Behnam Sanei; Mohsen Kolahdouzan; Hamid Reza Jafari; Mohammad Hossein Sanei (مجله دانشکده پزشکی اصفهان, 2016)
Background: Pancreaticouodenectomy (Whipple surgery) is the chosen treatment in patients with malignant or benign tumors of the pancreatic head. Pancreatic anastomosis is the most important part of Whipple surgery. Pancreatic fistula is the most common postoperative complication.